Political life writing in the Pacific : reflections on practice - Corbett, Jack; Lal, Brij V. (State, society and governance in Melanesia (Series), 2015)
This book emerged from a workshop symposium on political life writing held at The Australian National University (ANU) in October 2012. The inspiration came from discussions on the practice of life writing and the issues and challenges that one faces while writing political biography. Some of the themes related to life writing in general: the ambiguous place of the genre within the academy, its 'great person in history' tendencies, the relationship between writer and subject, and the big question that faces all writers: what to leave in and out. Also explored are the nature of certain source materials: Hansard's Parliamentary Debates, political speeches, interviews, and the divergent perspectives offered by supporters and opponents. Some of these themes seemed to be of particular significance in a Pacific context, including patterns of colonization and the memory of independence, issues elliptically captured by terms like 'culture' and 'tradition', the nature of 'self' presented in Pacific life writing, and the tendency for many of these texts to have been written by 'outsiders', or at least the increasingly contested nature of what that term means. With this broad canvas in mind, this book brings together, for the first time, a community of scholars writing 'political lives' in the Pacific.